2023
DOI: 10.30892/gtg.46108-1002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Climate Change in Natural Areas of the Turkestan Region of the Republic of Kazakhstan for the Purposes of Sustainable Agricultural and Recreational Nature Management

Abstract: The article presents the scientific results of a study for assessing climate change trends in natural areas of the Turkestan region of the Republic of Kazakhstan based on the use of long-term climate data (1940-2020) of sixteen meteorological stations located in the region. In the course of the study, tested domestic, international and proprietary methodology for assessing climate change in natural areas were used based on plotting a fixed time series of climatic indicators and the resulting equations of linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Figure 1. Map of natural areas of Turkestan region of the Republic of Kazakhstan Data sources The time series of the average annual temperature and annual precipitation indicators for 1941-2020 by sixteen weather stations represented in the following analytic databases: Kazgidromet RSE (Annual Bulletin, 2020), World Meteorological Organization (WMO) and in the "Weather and Climate" reference and information portal have been used as information support to assess the natural moisture availability of natural zones of the Turkestan region of the RK.The initial information for the allocation of natural areas of the Turkestan region was: materials of the field landscape research of contributors, landscape map of the Republic of Kazakhstan.An assessment of the homogeneity of climatic indicators (average annual air temperature and annual precipitation) in the territory of the Turkestan region on a spatio-temporal scale based on long-term data covering the period for 1941-2020 for 16 meteorological stations located in various natural zones using a linear trend was produced in the Microsoft program Excel , which showed that changes in climate indicators are statistically significant, confirming the heterogeneity of the time series ( Zh Mustafayev et al, 2023). .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Figure 1. Map of natural areas of Turkestan region of the Republic of Kazakhstan Data sources The time series of the average annual temperature and annual precipitation indicators for 1941-2020 by sixteen weather stations represented in the following analytic databases: Kazgidromet RSE (Annual Bulletin, 2020), World Meteorological Organization (WMO) and in the "Weather and Climate" reference and information portal have been used as information support to assess the natural moisture availability of natural zones of the Turkestan region of the RK.The initial information for the allocation of natural areas of the Turkestan region was: materials of the field landscape research of contributors, landscape map of the Republic of Kazakhstan.An assessment of the homogeneity of climatic indicators (average annual air temperature and annual precipitation) in the territory of the Turkestan region on a spatio-temporal scale based on long-term data covering the period for 1941-2020 for 16 meteorological stations located in various natural zones using a linear trend was produced in the Microsoft program Excel , which showed that changes in climate indicators are statistically significant, confirming the heterogeneity of the time series ( Zh Mustafayev et al, 2023). .…”
mentioning
confidence: 85%
“…An assessment of the homogeneity of climatic indicators (average annual air temperature and annual precipitation) in the territory of the Turkestan region on a spatio-temporal scale based on long-term data covering the period for 1941-2020 for 16 meteorological stations located in various natural zones using a linear trend was produced in the Microsoft program Excel , which showed that changes in climate indicators are statistically significant, confirming the heterogeneity of the time series ( Zh. Mustafayev et al, 2023) .…”
Section: Study Areamentioning
confidence: 99%
“…Turkestan region has a huge natural potential for the development of the economy and food security of the Republic of Kazakhstan (Mukayev et al, 2022), since it has an adequate supply of mineral resources, fertile soil, abundance of sunlight and extensive natural fodder resources (pastures), which makes it possible to develop various branches of agriculture in the region, primarily, irrigated cropping and range sheep production using available water resources (Mustafayev et al, 2023). Water resources are essential elements for any touristic destination (Aliyev and Suleymanov, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studying climate changes using long-term climate indexes for 1941-2020 from 16 weather stations located in various natural and climatic zones of the Turkestan region showed that the average annual air temperature increased by 15-20% and annual precipitation decreased by 10-20% [1], which is a serious signal that calls for improvement of the natural scientific understanding of modern ecological and landscape mechanisms for the assessment of the agro-resource potential of landscapes in the conditions of a changing climate.…”
Section: Introductionmentioning
confidence: 99%